Square Difference Labeling for Pyramid Graph and its Related Graphs - P. Jagadeeswari; K. Ramanathan; K. Manimekalai (International Journal of Mathematics And its Applications, 2018)
In this paper, we prove the characterization of pyramid graph (n ≥ 3), hanging pyramid graph and the associated graphs admits square difference labeling.